Polymorphisms in canine immunoglobulin heavy chain gene cluster: a double‐edged sword for diabetes mellitus in the dog. (23rd February 2021) - Sanz, C. R.; Sevane, N.; Pérez‐Alenza, M. D.; Valero‐Lorenzo, M.; Dunner, S.
Summary: Insulin deficiency diabetes (IDD) in dogs is an endocrine disease similar to human type 1 diabetes. There are breeds more commonly affected, such as Yorkshire Terrier and Samoyed, suggesting an underlying genetic component. However, the genetic basis for canine diabetes mellitus (DM) is not fully established. We conducted both whole‐genome scans for selection signatures and GWASs to compare the genomes of 136 dogs belonging to 29 breeds previously described at low or high risk for developing DM. Candidate variants were tested in dogs with a diagnosis of IDD and controls attending the Complutense Veterinary Teaching Hospital. The only genomic region under selection (CFA8:72 700 000–74 600 000; CanFam3.1) retrieved by our analyses is included in the immunoglobulin heavy chain gene cluster, which has already been related to human human type 1 diabetes susceptibility. This region contains two non‐synonymous variants, rs852072969 and rs851728071, showing significant associations with high or low risk for IDD, respectively. The first variant, rs852072969, alters a protein poorly characterised in the dog. In contrast, rs851728071 was predicted to block the synthesis of an immunoglobulin variable (V) domain in breeds at low risk for DM. Although a large and diverse V gene repertoire is thought to offer a fitness advantage, we suggest that rs851728071 prevents the formation of an auto‐reactive immunoglobulin V domain probably involved in the pathophysiology of IDD and, thus, decreases the risk for the disease. These results should be interpreted with caution until the functional roles of the proposed variants have been proved in larger studies.